A Longitudinal Seroconversion Panel Shows Anti-SARS-CoV-2 Antibody Levels up to 6.5 Months After Vaccination with mRNA-1273 (Moderna). (October 2022) - Belda, Francisco; Mora, Oscar; Christie, Rebecca; Crowley, Michael
BACKGROUND: Vaccines have emerged as a crucial tool in combatting the COVID-19 pandemic particularly those based on SARS-CoV-2 S-protein mRNA. A crucial aspect of vaccine efficacy is the duration of antibody responses. In this study, a seroconversion panel was created to assess antibody responses to the mRNA-1273 vaccine over time (6.5 months). METHODS: Blood samples collected from 15 healthy adult participants prior to and up to 6.5 months after vaccination with the mRNA-1273 vaccine (Moderna). Serum from these blood samples were analyzed for anti-SARS-CoV-2 antibody activity by chemiluminescent immunoassay. RESULTS: The immunoassay results showed that one participant was positive for anti-SARS-CoV-2 antibodies prior to vaccination indicating a prior infection. All participants showed a positive antibody response after the first vaccination. Highest antibody responses were seen after the second dose (41-45 days from the first dose). Subsequent samples collected at 69-75 days, 130-135 days, and 221-229 days after the first vaccination showed positive responses but a biphasic decline in the levels of anti-SARS-CoV-2 antibodies. CONCLUSIONS: Declining antibody levels in these participants support the use of booster vaccination to increase antibody levels 4-6 months after the initial vaccine series and continued monitoring to assess the durability of COVID-19 vaccine responses. These results are in agreement with other studies showing antibody persistence but declining the antibody levels in the months after immunization with mRNA-based vaccines. The seroconversion panels described here could be useful in the development of antibody assays and in the assessment of the duration of antibody responses to vaccine boosters compared to the initial vaccine series. This panel could also be used to assess antibody activity against emerging viral variants (eg B.1.1.529 [Omicron] and its subvariants) compared to earlier variants.